DARI PINGGIR: MEMBANGUN ARSIP, MENYINTASKAN KEDAULATAN: Array - Fauzan Anyasfika (Jurnal Kearsipan, 2017)
Developing the border areas is a part of the Government's commitment set forth in the Nawacita (it is the national development agenda for Indonesia that has been declared by President Jokowi). In developing the areas, the government should refer to the strategic environment including the disputes on territorial ownership that might happen. Thus, the Government should be able to prove the ownership of the border areas with data and facts. The data and facts that contain information on border areas are archives. An active role is required to ensure the availability of the archives of the border areas. With these evidences, the development in these areas will run smoothly. And eventually, the archive will hold its function as a tool to prevent the sovereignty of Unitary Nation of the Republic of Indonesia’s territory.